2019
DOI: 10.2136/sssaj2018.08.0302
|View full text |Cite
|
Sign up to set email alerts
|

Soil Compaction Effects on Root‐Zone Hydrology and Vegetation in Boreal Forest Clearcuts

Abstract: Core Ideas Impact of forwarding on soil water and vegetation was investigated after 4 to 5 years. Soil water content was highest in wheel tracks and lowest between tracks. Bare soil was more frequent in tracks and between tracks than in undisturbed soil. In wheel tracks, soil aeration may be restricted in periods with high precipitation. Simulated root‐zone pressure heads showed little variation between microsites. Soil compaction is a common consequence of forestry traffic traversing unprotected, moist soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…For example, soil compaction and land degradation are typically associated with increased overland flow and faster delivery of water to the streams (Hallett et al, ; O'Connell et al, ), thus shortening travel times. Within the upper part of the soil itself, we found that the podzol, which was relatively compacted due to grazing (Singleton, Boyes, & Addison, ) and as a consequence with increased water holding capacity (Hansson, Šimůnek, Ring, Bishop, & Gärdenäs, ), had a longer MTT (~3 months) than the gley soils (~1 month), which were regularly ploughed. In agreement, the measured topsoil SWC in the cropped fields (with gleys) was always lower than in the pasture (with podzols).…”
Section: Discussionmentioning
confidence: 90%
“…For example, soil compaction and land degradation are typically associated with increased overland flow and faster delivery of water to the streams (Hallett et al, ; O'Connell et al, ), thus shortening travel times. Within the upper part of the soil itself, we found that the podzol, which was relatively compacted due to grazing (Singleton, Boyes, & Addison, ) and as a consequence with increased water holding capacity (Hansson, Šimůnek, Ring, Bishop, & Gärdenäs, ), had a longer MTT (~3 months) than the gley soils (~1 month), which were regularly ploughed. In agreement, the measured topsoil SWC in the cropped fields (with gleys) was always lower than in the pasture (with podzols).…”
Section: Discussionmentioning
confidence: 90%
“…Here it is necessary to differentiate into positions of tracks, ruts, cut slope, fill slope, and area between the tracks or ruts (Fig. 2), as these various positions have a markedly different effect on vegetation regeneration (Youngberg 1959;Kennard 1998;Brais 2001;Hansson et al 2019). These differential responses are because the tracks experience the greatest compaction followed by, to a lesser degree, the center of the trail (Dickerson 1976;Allbrook 1986;Jusoff 1988;Ole-Meiludie and Naju 1989).…”
Section: Regenerationmentioning
confidence: 99%
“…For example, on a wet forest site in Australia, Williamson and observed that this regeneration was not sustained over time. Regeneration in the tracks or ruts of skid trails tend to be shorter and contain less biomass than other areas of the trails (Hatchell et al 1970;DeArmond et al 2019;Hansson et al 2019). These impacts are also observed belowground, as Picchio et al (2019) found greater root lengths and rooting depths between the tracks.…”
Section: Regenerationmentioning
confidence: 99%
“…Li et al, 2018;Liu et al, 2015;Zhang et al, 2001). However, vegetation restoration can increase soil porosity and soil infiltration, thereby promoting groundwater recharge and possibly baseflow (Gu et al, 2018;Hansson et al, 2019;Liu et al, 2015). Since large-scale changes in vegetation could induce regional changes in both precipitation and ET, there could be a divergent hydrological response to large-scale changes in vegetation, including afforestation (Farley et al, 2005; and deforestation (Q.…”
Section: Introductionmentioning
confidence: 99%
“…Paired basin studies show a general consensus that vegetation greening (browning) leads to a decrease (increase) in mean streamflow due to increased (decreased) canopy interception and vegetation transpiration (Bosch & Hewlett, 1982; Brown et al, 2005; Cheng et al, 2017; Q. Li et al, 2018; Liu et al, 2015; Zhang et al, 2001). However, vegetation restoration can increase soil porosity and soil infiltration, thereby promoting groundwater recharge and possibly baseflow (Gu et al, 2018; Hansson et al, 2019; Liu et al, 2015). Since large‐scale changes in vegetation could induce regional changes in both precipitation and ET, there could be a divergent hydrological response to large‐scale changes in vegetation, including afforestation (Farley et al, 2005; Y. Li et al, 2018) and deforestation (Q. Li et al, 2018; Liu et al, 2015; Spracklen et al, 2012; Staal et al, 2018).…”
Section: Introductionmentioning
confidence: 99%